Credit access by smallholder livestock producers and implications for technology adoption: Policy options for improving the credit delivery system in South Vietnam. - Ho Cao Viet; Lapar, Ma. Lucila; Aragón, C. (International Livestock Research Institute, 2004)
This study describes the existing credit policies and programs in South Vietnam that are related to smallholder livestock production and Development; evaluates the implementation of current credit delivery systems and their impacts on farmers, focusing on implications for technology adoption by smallholder livestock farmers; and identifies and recommends policy options for improving the effectiveness of credit policies and institutions for smallholders. This study not only is based on theoretical aspects but also carries out a practical investigation with the participation of all agents involved in rural credit performance: farmers (borrowers and non-borrowers), banking and credit specialists, banking staff, researchers, and local authorities. The survey is conducted in a village with a gathering of the clientele of a credit program that was implemented in rural areas as a case study. The theoretical approach of this study is illustrated in a chart. The document starts with definitions and principal concepts of credit; banking systems; savings, and guarantee funds. Then it discusses the policy environment for credit in Vietnam; review of credit policies and documents related to existing credit delivery systems; status quo of the credit system in Vietnam; demand for capital by rural areas and farmer households; smallholder farmers'access to credit; the main constraints of the credit system in Vietnam; a case study of credit delivery system in South Vietnam; the credit delivery system in Dong Tam village; income and expenditures; use of the Loan; factors determining access to credit by farmers in Dong Tam village; land title as collateral: the missing element; and an assessment of the existing credit delivery system. Six models which are built on lessons learned from other projects carried out in similar regions are also presented as options for the credit program to follow. The Report ends with conclusions and policy implications drawn from the findings of the study.